Анализ энергоэффективности режимов работы электрических систем с тяговыми нагрузками - Бондаренко, В.О; Доманский, И.В.; Костин, Г.Н (Електротехніка і електромеханіка, 2017)
В статье предложены инновационные направления энергосбережения в тяговых сетях железных дорог и новые схемотехнические решения присоединения тяговых подстанций к сетям энергосистем, обеспечивающие энергобезопасность перевозочного процесса. Дано обоснование необходимости расчета тяговых подстанций по векторному методу
трехфазного потребления энергии от подстанций НЭК «Укрэнерго». У статті запропоновані інноваційні напрямки енергозбереження в тягових мережах залізниць і нові схемотехнічні
рішення приєднання тягових підстанцій до мереж енергосистем, що забезпечують енергобезпеку процесу перевезень.
Дано обґрунтування необхідності розрахунку тягових підстанцій по векторному методу трифазного споживання
енергії від підстанцій НЕК «Укренерго». Innovative scenarios of reliable energy supply of transportation
process aimed at reducing the specific energy consumption and
increase energy efficiency of the systems of electric traction. The
paper suggests innovative energy saving directions in traction
networks of railways and new circuit solutions accessing traction
substations in energy systems networks, ensure energy security of
the transportation process. To ensure the energy security of rail
transport special schemes were developed to propose the concept
of external power traction substations, which would increase the
number of connections to the networks of 220 – 330 kV, as well as
the creation of transport and energy corridors, development of its
own supply of electric networks of 110 kV substations and mobile
RP-110 kV of next generation. Therefore, the investment program
of the structures owned by the Ukrainian Railways (Ukrzaliznytsia) need to be synchronized in their technological characteristics,
as well as the criteria of reliability and quality of power supply
with the same external energy investment programs. It is found
that without any load on left or right supplying arm one of two
less loaded phases of traction transformer begins generating specific modes in the supplying three-phase line. Thus, modes of mobile substation cause leakage in one of the phases of the supply
line of traction transformers of active-capacitive current, and as a
result generating energy in the main power line of 154 kV, which
is fixed and calculated by electricity meters. For these three phase
mode supply network is necessary to use 1st algorithm, i.e. taking
into account the amount of electricity as the energy in all phases.
For effective application of reactive power compensation devices
in the AC traction power supply systems it is proposed to develop
regulatory documentation on necessity of application and the
order of choice of parameters and placement of compensation
systems taking into account operation mode of power systems and
the use of software systems with imitation of instantaneous interrelated schemes of transport loads.